The Relationship Between The Level Of Knowledge Of Kiasu Culture And The Way Of View Of High School / Vocational School Students In The City Of Surabaya To Achieve Golden Indonesia - Husnul Kirom Ramadhani; Aldyandi, Devlin (Universitas Nahdlatul Ulama Surabaya, 2024)
Kiasuism is defined as a competitive attitude to achieve a better life without depriving others of their rights. Kiasu culture is applied in the social life of Singaporeans, changing people who previously had fear and lack of focus in self-regulation that hindered creativity into people who have a good mentality and high competitiveness. The research was a quantitative study using a questionnaire with high school / vocational high school students as respondents. The determination of many samples uses the slovin formula while determining respondents using cluster sampling and simple random sampling. the results of this study found that there were still many students who did not know about kiasu culture but most of them have applied several indicators of kiasu culture. The results of this study can be developed to contribute ideas for various parties in the context of improvement of daily learning culture so as to improve learning outcomes learning outcomes in high school / vocational high school students in Surabaya City. Keywords: Application of kiasu culture, definition of kiasu, positive impact of kiasu culture, survey